2012
DOI: 10.1007/s00425-012-1730-y
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of COP1 in ethylene- and light-regulated hypocotyl elongation

Abstract: Ethylene and light act through specific signal transduction mechanisms to coordinate the development of higher plants. Application of 1-aminocyclopropane-1-carboxylic acid (ACC, an ethylene precursor) suppresses the hypocotyl elongation of Arabidopsis seedlings in dark, but stimulates it in light. However, the mechanisms of opposite effects of ethylene on hypocotyl elongation in light and dark remain unclear. In the present study, we investigated the key factors involved in the opposite effects of ethylene on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 50 publications
4
30
1
Order By: Relevance
“…In support, ethylene was shown to depend on HY5 in the regulation of hypocotyl growth in the light but not in darkness (Liang et al, 2012;Yu et al, 2013). HY5 emerged as an inhibitor of ethylene during hypocotyl growth in the light.…”
Section: Ethylene and Hypocotyl Growthmentioning
confidence: 97%
See 2 more Smart Citations
“…In support, ethylene was shown to depend on HY5 in the regulation of hypocotyl growth in the light but not in darkness (Liang et al, 2012;Yu et al, 2013). HY5 emerged as an inhibitor of ethylene during hypocotyl growth in the light.…”
Section: Ethylene and Hypocotyl Growthmentioning
confidence: 97%
“…Conversely, in darkness, COP1 acts upstream of EIN3. Both ethylene and overexpression of EIN3 reduced the expression of ETHYLENE RESPONSE FACTOR1 (ERF1) in etiolated wild-type seedlings, whereas in dark-grown cop1 seedlings, ERF1 expression was enhanced, suggesting that COP1 regulates the transcriptional activity of EIN3 (Liang et al, 2012). Apart from COP1, photomorphogenesis is also repressed in the dark by PHYTOCROME INTERACTING FACTORS (PIFs; Leivar and Quail, 2011;Lau and Deng, 2012).…”
Section: Ethylene and Hypocotyl Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Liang et al showed how loss-of-function mutants for auxin receptor TIR1 (tir1-1) grown in the dark are shorter than wild-type plants, suggesting that not only BR-signaling but also AX-signaling affects plant growth in the dark. 27) In contrast, when seedling were treated with Brz in the dark, photomorphogenesis, including cotyledon development and the suppression of etiolation, was induced in a clear dose-dependent manner in the range of 0.3-3 μM (Fig. 2(a)).…”
Section: Effect Of Nj15 On Br-signaling In the Darkmentioning
confidence: 99%
“…FAR-RED ELONGATED HYPOCOTYL3 (FHY3) and FAR-RED IMPAIRED RESPONSE1 (FAR1), two key transcription factors in the PhyA signaling pathway, directly bind to the ABA-insensitive (ABI5) promoter to modulate ABA signaling in Arabidopsis (Tang et al, 2013). PHYTOCHROME-INTERACTING FACTOR5 (PIF5) and COP1 have a role in ethylene biosynthesis and ethylene-regulated hypocotyl elongation (Khanna et al, 2007;Liang et al, 2012). Brassinosteroids (BRs) are one of the important groups of plant hormones that have been studied for their crucial role in regulating morphological processes, especially cell elongation .…”
Section: Introductionmentioning
confidence: 99%